Effet De La Fertilisation Phospho-Potassique Sur Le Rendement Grainier Et La Qualite Des Semences De Cajanus Cajan L. Millsp. Sur Un Ferrasol A Yamoussoukro, Region Centre De La Cote Dâ€™ivoire - Koutouan, Faustin P.; Nguessan, Bodji C; Wandan, Eboua N.; Ta Bi, DjÃ©hi B. (European Scientific Journal, ESJ, 2017)
The aim of the present work was to evaluate the effect of phosphorus and potassium fertilization on the production and the quality of pigeon pea seeds produced on a ferrasol type sol. A completely randomized block design was used, in a 2x3x3 factorial set with three replications. A density of 20 000 plants ha -1 was used. The treatments were 0, 40, 80, units for phosphorus (P2O5) and potassium (KCl). Treatment which received P80K80 fertilization had greater productivity (650 kg) but a low germination rate (30 %). The optimal dose (523 kg and 90 % germination rate) was obtained with P40K80, followed by P40K40 dose (516 kg and 82 % germination rate). Phosphorus and potassium had mutually acted and influenced positively the production and the quality of the seeds of C. cajan.